RhoC Modulates Cell Junctions and Type I Interferon Response in Aggressive Breast Cancers - Abraham, Hannah G.; Ulintz, Peter J.; Goo, Laura; Yates, Joel A.; Little, Andrew C.; Bao, Liwei; Wu, Zhifen; Merajver, Sofia D. (Frontiers in Oncology, 2021)
Metastases are the leading cause of death in cancer patients. RhoC, a member of the Rho GTPase family, has been shown to facilitate metastasis of aggressive breast cancer cells by influencing motility, invasion, and chemokine secretion, but as yet there is no integrated model of the precise mechanism of how RhoC promotes metastasis. A common phenotypic characteristic of metastatic cells influenced by these mechanisms is dysregulation of cell-cell junctions. Thus, we set out to study how RhoA- and RhoC-GTPase influence the cell-cell junctions in aggressive breast cancers. We demonstrate that CRISPR-Cas9 knockout of RhoC in SUM 149 and MDA 231 breast cancer cells results in increased normalization of junctional integrity denoted by junction protein expression/colocalization. In functional assessments of junction stability, RhoC knockout cells have increased barrier integrity and increased cell-cell adhesion compared to wild-type cells. Whole exome RNA sequencing and targeted gene expression profiling demonstrate decreased expression of Type I interferon-stimulated genes in RhoC knockout cells compared to wild-type, and subsequent treatment with interferon-alpha resulted in significant increases in adhesion and decreases in invasiveness of wild-type cells and a dampened response to interferon-alpha stimulation with respect to adhesion and invasiveness in RhoC knockout cells. We delineate a key role of RhoC-GTPase in modulation of junctions and response to interferon, which supports inhibition of RhoC as a potential anti-invasion therapeutic strategy.